Resveratrol Enhances the Anti-Cancer Effects of Cis-Platinum on Human Cervical Cancer Cell Lines by Activating the SIRT3 Relative Anti-Oxidative Pathway - Jiang, Bin; Tian, Qi; Shu, Chuqiang; Zhao, Jing; Xue, Min; Zhu, Shujuan (Frontiers in Pharmacology, 2022)
Background Cervical cancer exerts considerable mortality in world. The combinations of chemotherapy with cis-platinum were the first-line treatment in late stage cervical cancer but may cause severe adverse effects. Resveratrol is a phytoalexin and it showed anti-cancer effects but with low toxicity and side effect. Herein, we examined the anti-cancer effects of cis-platinum combined with resveratrol in human cervical cancer cell lines. Methods The antiproliferative effect was examined by cell counting and short-term MTT assay. Cell apoptosis was detected and cell cycle distribution was determined by flow cytometry. Intracellular reactive oxygen species and mitochondrial transmembrane potential change were observed and calculated by confocal microscopy. The Si-RNA interference of SIRT3 in cancer cells was performed. Protein expression was checked by western blotting. Results Resveratrol inhibited the growth of SiHa cell lines and it significantly enhanced the cis-platinum induced cell apoptosis and cell cycle arresting in 48 hours. Investigation of the mechanism of action, revealed that the enhanced anti-cancer effects of cis-platinum and resveratrol combination were due to the activating of SIRT3 relative anti-oxidative pathway. Si-RNA interference of SIRT3 compromised the anti-cancer effect of cis-platinum and resveratrol combination. Furthermore, the silencing of SIRT3 RNA inhibited the expression of anti-oxidant enzyme (MnSOD, GPx, CuZnSOD CAT) and decreased the generation of H2O2 in the cis-platinum and resveratrol combination group. Conclusion Resveratrol enhances the anti-cancer effects of cis-platinum on SiHa cells by activating the SIRT3 relative anti-oxidative pathway. Resveratrol may act as a potential synergistic agent and be useful in the treatment of cervical cancer.